An outbreak of crayfish rickettsiosis caused by Coxiella cheraxi in redclaw crayfish (Cherax quadricarinatus) imported to Israel from Australia. Issue 2 (10th November 2021) - Davidovich, Nadav; Fiocchi, Eleonora; Basso, Andrea; Budai, Jane; Montesi, Francesco; Pretto, Tobia
Abstract: The redclaw crayfish ( Cherax quadricarinatus ) is a freshwater decapod crustacean, cultured in numerous countries worldwide for both food and ornamental purposes. Redclaw crayfish has become an important aquaculture species due to its physical and biological traits, relatively easy breeding, and a short growing‐out period to reach commercial size. Bacterial infections are the second‐most studied pathogens of freshwater crayfish. However, redclaw crayfish rickettsiosis, caused by Coxiella cheraxi, was reported in only a few scientific papers in the early 2000s, in Australia and Ecuador. Coxiella cheraxi is a rod‐shaped intracellular bacterium that can cause mortality of 22%−80% in naturally infected crayfish. In experimental infections, mortality rates may be even higher (40%−90%). Coxiella cheraxi is closely related to Coxiella burnetii, the agent of Q‐fever, which affects ruminants (goats, sheep, and cattle) and occasionally may cause zoonotic infections. According to the scientific knowledge available, C. cheraxi is a species‐specific pathogen because it has been only detected in Cherax quadricarinatus and thus far, there is no evidence of a zoonotic potential. In this study, we describe an outbreak of rickettsiosis in a batch of redclaw crayfish imported to Israel from an Australian hatchery, observed 2 months after introduction in a quarantine facility. Initial mortality was evaluated through histopathology, revealing infection by rickettsia‐like organisms (RLO) that were subsequently investigated by molecular analysis and transmission electron microscopy examination. Phylogenetic analysis revealed that the detected RLO were closely related to C. cheraxi from a single source (Australian strain TO98), available in free publicly accessible databases. After 5 months in quarantine, almost 99% of the crayfish population had died. Our findings raise valuable questions related to aquatic animal trade and the importance of mitigation measures, such as quarantine and routine diagnostic procedures, to limit the spread of infectious diseases.